EXPERIMENTAL THERAPEUTIC EVALUATION OF THE AFRICAN VEGETABLES (CLERODENDRUM VOLUBILE LEAF AND IRVINGIA GABONENSIS SEED EXTRACTS) IN TRASTUZUMAB-MEDIATED HEPATO-RENAL DYSFUNCTION IN WISTAR RATS - ADENEYE, ADEJUWON; OLORUNDARE, OLUFUNKE; AKINSOLA, AKINYELE; SOYEMI, SUNDAY; MGBEHOMA, ALBAN; OKOYE, IKECHUCKWU; ALBRECHT, RALPH; NTAMBI, JAMES; MUKHTAR, HASAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The use of trastuzumab (TZM) in the clinical management of human epidermal growth factor receptor 2 positive metastatic breast and gastric cancers, gastro-esophageal adenocarcinoma, and colorectal carcinoma has been limited by its off-target cardiac, hepatic, and renal toxicities which till date have no effective therapies in either their prevention or amelioration. Thus, the present study is designed at investigating the protective and therapeutic potentials of 400 mg/kg/day Clerodendrum volubile ethanol leaf extract (CVE) and Irvingia gabonensis ethanol seed extract (IGE) pretreatments in TZM-intoxicated Wistar rats based on their reported folkloric use in the local management of kidney and liver diseases and the previously reported therapeutic potential of these African vegetables in TZM cardiotoxicity. Methods: Forty-nine male Wistar rats were randomly allotted into seven groups of seven rats per group. Group I rats were treated with 10 ml/kg/day of 5% dimethyl sulfoxide (DMSO) sterile water p.o. and 1 ml/kg/day 5% DMSO sterile water i.p.; Groups II and III rats were orally pretreated with 400 mg/kg/day CVE and IGE, respectively, 3 h before 1 ml/kg/day/i.p. 5% DMSO sterile water; Group IV rats were orally pretreated with 10 ml/kg/day 5% DMSO sterile water 3 h before 2.25 mg/kg/day/i.p. TZM; and Groups V-VII rats were pretreated with 20 mg/kg/day Vit. C, 400 mg/kg/day CVE, and 400 mg/kg/day IGE all dissolved in 5% DMSO sterile water, respectively, 3 h before i.p. injections of 2.25 mg/kg/day TZM, all for 7 days. Liver function parameters, renal function parameters, oxidative stress markers, and histopathological investigations were the study measuring endpoints. Results: Oral pretreatment with 20 mg/kg/day Vit. C, 400 mg/kg/day CVE and IGE significantly ameliorated TZM-mediated hepatic and renal toxicities by effectively lowering the serum alanine transaminase, aspartate transaminase, alkaline phosphatase, creatinine, and urea levels. CVE and IGE pretreatments also significantly reversed TZM-induced decreases in the hepatic and renal tissue catalase, superoxide dismutase, and glutathione- S-transferase activities and reduced malondialdehyde levels. CVE and IGE pretreatments also improved TZM-induced hepatic and renal histological lesions. Conclusions: Overall, the chemotherapeutic/chemopreventive potentials of CVE and IGE in TZM-induced hepatorenal dysfunction were either wholly or partly mediated through free-radical scavenging and antioxidant activities.